2022
DOI: 10.1007/s12144-022-02864-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-mood knowledge moderates the relationship between neuroticism and depression but not between neuroticism and anxiety in a sample of nonclinical adolescents

Abstract: Research shows a strong link between neuroticism and internalizing psychopathology, such as depression and anxiety. However, it is unclear to what extent meta-mood knowledge (i.e., attention to emotion and emotional clarity) plays a role as a moderator in this relationship. To investigate this, we collected data on meta-mood knowledge, personality traits, depression, and anxiety in a sample of adolescents (N = 244; 53.7% girls) aged 12 to 18 years (M = 14.6, SD = 1.7) from Catalonia, Spain. Regarding the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Other studies, more focused on the relationship between emotional intelligence and emotional distress [ 28 ], showed that high levels of emotional attention have been related to greater emotional distress [ 28 ]. Regarding the dimension of emotional repair, the results obtained by different researchers are in the same direction as those found in the present investigation [ 27 , 32 ], although these studies do not analyze the role mediator of negative affect in the relationship between neuroticism and emotional intelligence, so our results are revealing at an explanatory and empirical level in this sense. This work probably supports the results of Aluja [ 49 ] on the neuroticism construct, allowing us to know how its components operate psychologically (mediating or moderating) in our case, in the explanation of the relationship between neuroticism and emotional intelligence.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Other studies, more focused on the relationship between emotional intelligence and emotional distress [ 28 ], showed that high levels of emotional attention have been related to greater emotional distress [ 28 ]. Regarding the dimension of emotional repair, the results obtained by different researchers are in the same direction as those found in the present investigation [ 27 , 32 ], although these studies do not analyze the role mediator of negative affect in the relationship between neuroticism and emotional intelligence, so our results are revealing at an explanatory and empirical level in this sense. This work probably supports the results of Aluja [ 49 ] on the neuroticism construct, allowing us to know how its components operate psychologically (mediating or moderating) in our case, in the explanation of the relationship between neuroticism and emotional intelligence.…”
Section: Discussionsupporting
confidence: 86%
“…With these data, we partially confirm our second hypothesis. In this regard, the findings of Yildirim et al [ 27 ] in their study on the relationship between neuroticism and depression, showed that low levels of emotional attention, in combination with high levels of emotional clarity, facilitated emotional self-awareness, a finding that should be further explored. Regarding emotional clarity, in our opinion, we hypothesize that perhaps emotional clarity responds to different psychological mechanisms, which may involve other combinations of the variables studied, to the mechanisms of attention and emotional repair, an assumption that requires the realization of new research studies in this regard.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, longitudinal studies have also found that neuroticism is still predictive of depressive symptoms 2 years later ( Van Loey et al, 2014 ). Additionally, some studies reported that depression scores are positively and significantly associated with neuroticism among healthy subjects ( Yoon et al, 2013 ; Yildirim et al, 2022 ). Another longitudinal study found that neuroticism is consistently associated with depressed emotion in a sample of healthy college students ( Yao et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%